An Analysis of Direct and Indirect Speech Acts Performed by the Main Character in the Movie Doctor Strange in The Multiverse Madness - Florensia Elkesin Hamnu; I Gde Agoes Caskara Surya Putra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study aimed to describe the types of direct and indirect speech acts, as well as the dominant types used in the Doctor Strange movie. The focus is on analyzing the direct and indirect speech act utterances performed by the main character of “Doctor Strange in The Multiverse Madness movie”. The data was examined using the method of descriptive qualitative analysis which was also presented in informal and formal ways. The researcher used some techniques for collecting the data as follows. First, download the “Doctor Strange in The Multiverse Madness Movie”, and the movie script. Second, watching the movie twice or more, and reading the script. Third, taking note of classifying based on the types. The findings show that there are 29 types of direct speech act found in the movie, as follow. 6 data of declarative sentences, 14 data of interrogative sentences, and 9 data of imperative sentences. Meanwhile for indirect speech acts found there are 5 data interrogative, 4 data declarative, and 4 data for imperative. As a result, the most dominant used in this study was interrogative sentences as a type of direct speech act.